2019
DOI: 10.1136/bcr-2018-228479
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and choroidal circulation determined by optical coherence tomography angiography in patient with amyloidosis

Abstract: A 43-year-old woman who was diagnosed with the cryopyrine-associated periodic syndrome (CAPS) with severe renal failure and heart failure due to amyloid accumulation was examined by swept source optical cohernce tomography (OCT) (SS-OCT; DRI-OCT, Topcon, Tokyo, Japan) and optical coherence tomography angiography (OCTA) (RTVue XR Avanti, Optovue, Fremont, CA). Her best-corrected visual acuity was 20/40 OD and 20/25 OS. A hyporeflective band of about 100 µm thickness was seen just inferior to the retinal pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…The authors established that more severe stages of amyloid choroidopathy correlated with worse clinical scores of systemic disease. Similar to some prior reports, 5 , 7 macular OCT in our patient revealed a thickened sub-RPE/Bruch's hyporeflective band associated with relatively thickened choroid and thinning of the ONL.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The authors established that more severe stages of amyloid choroidopathy correlated with worse clinical scores of systemic disease. Similar to some prior reports, 5 , 7 macular OCT in our patient revealed a thickened sub-RPE/Bruch's hyporeflective band associated with relatively thickened choroid and thinning of the ONL.…”
Section: Discussionsupporting
confidence: 91%
“…In general, involvement of the retina or the choroid is not typical in systemic amyloidosis with a limited number of cases reported. 4 , 5 , 6 , 7 This report describes a case of a patient with retinochoroidal involvement from systemic light-chain amyloidosis whose fluorescein angiography demonstrated dark choroid - a finding that has not has not been previously reported in this condition.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…If this is just a local finding or similar changes could be found in other organs remains an unsolved question. Other studies have suggested VD in central retina as a possible vascular biomarker and examined its relationship with systemic conditions: diabetes, 23 chronic kidney disease, 24 inflammatory bowel disease, 25 amyloidosis 26 or Alzheimer, 26 so could VD be considered a biomarker for microvascular abnormalities after the infection of SARS-CoV-2? Longitudinal studies over time will be necessary to assess vascular outcomes in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Common ocular manifestations of amyloidosis include amyloid deposition in the ocular adnexa, conjunctiva, cornea, trabecular meshwork and/or the vitreous, however retinal and choroidal involvement is rare. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Histopathological analysis of amyloid deposition in the choroid has been reported in cases of systemic primary amyloidosis. 17 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%